BEBERAPA MASALAH ERGONOMIK DALAM KEGIATAN PENEBANGAN DI KALIMANTAN BARAT - Maman Mansyur Idris; Zakaria Basari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
Preliminary study on ergonomics of forest concession was emphasized on mechanic operator activities with 62 respondents. The quetioneire consits of ten problem areas, namely audiometry, pollution, vibration, phisycal work load, logging equipment operation, work capacity, psychology of work load, accident, safety, and the inventory of past ergonomic research. In general, the research indicated that the forest concession holders were not well aware of the importance of ergonomic aspect in their ventures.